ANALISIS KOMODITAS UNGGULAN SUB SEKTOR PERKEBUNAN DI KABUPATEN SINTANG - SETIYADI, B61111009 (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT Based on the value of regional gross domestic product in 2008 to 2012 were obtained from the central body of statistics in Sintang district, the agricultural sector is a major driver in the economy sector in Sintang district. Plantation sector is a sub –sector contributed the most to the agricultural sector in the district Sintang. If the plantation sub–sector in Sintang district managed properly, it can improve the economic and social welfare in Sintang district. The title of this research is the analysis of the leading commodity in the plantation sector sub Sintang district. The purpose of this research is to identifty the commodities plantation sub – sector in Sintang district and analyze various sub – sector leading commodity plantation in Sintang district. The analysis method used in this research is the analysis of Location Quotient. Shift Share analysis and analysis of Typology Klassen. The result of this research showed the leading commodity plantation sub – sektor in Sintang distirct is rubber, palm oil, and pepper. Commodities that are not featured on the plantation sector sub sintang district are coconut, hybrid coconut, coffe, cocoa, and various plants. Commodity in the plantation sector sub Sintang distirct that quite advanced and fast growing rubber, palm oil, and pepper. Commodity is relatively fast growing hybrid coconut, coffee, cocoa, and various plants. Commodities that are relatively lagging is coconut and no commodity is more advanced but grow slowly. Keyword : Agriculture, Plantationt sub–sector, Commodities and leading commodity.